Nanotechnology in Sustainable Agriculture: Recent Developments, Challenges, and Perspectives - Prasad, Ram; Bhattacharyya, Atanu; Nguyen, Quang D. (Frontiers in Microbiology, 2017)
Nanotechnology monitors a leading agricultural controlling process, especially by its miniature dimension. The application of nanotechnology to agriculture and food industries is resonant increased encumbrance because of the potential benefits ranging from enhanced food quality, safety to reduced agricultural inputs and enriched absorbing nanoscale nutrients from the soil. Agriculture, food and natural resources are a part of those challenges like sustainability, susceptibility, human health and healthy life. The ambition of nanomaterials in agriculture is to reduce the amount of spread chemicals, minimize nutrient losses in fertilization and increased yield through pest and nutrient management. Nanotechnology has the prospective to improve the agriculture and food industry with novel nanotools for the controlling of rapid disease diagnostic, enhancing the capacity of plants to absorb nutrients among others. The significant interest of using nanotechnology in agriculture includes specific applications like nanofertilizers and nanopesticides to trail products and nutrients levels to increase the productivity without decontamination of soils, waters and protection against several insect pest and microbial diseases. Nanotechnology may act as sensors for monitoring soil quality of agricultural field and thus it maintain the health of agricultural plants.This study provides a review of the current challenges of sustainability, food security and climate change that are exploring by the researchers in the area of nanotechnology in the improvement of agriculture.